Influence of Trichosanthes pericarpium extract on improving microcirculation and outcomes of patients with acute myocardial infarction after percutaneous coronary intervention - Xi, Peng; Xie, Yuan; Huang, Feifei; Liu, Yang; Xu, Jiahong (Frontiers in Cardiovascular Medicine, 2024)
Background: Microcirculatory dysfunction is an independent risk factor for a poor prognosis after percutaneous coronary intervention (PCI) in patients with acute myocardial infarction (AMI).Trichosanthes pericarpium is a well-known Chinese traditional herb described with the effect of activating blood circulation to dissipate blood stasis and improve blood circulation. However, its effects on microcirculation in patients with AMI after primary PCI remain unknown. This study aimed to investigate the effect of Trichosanthes pericarpium extract (TPE) on improving microcirculation and outcomes in patients with AMI after PCI.Methods: This study included 155 patients with a history of emergency PCI treatment. In this cohort, 31 patients received a course of TPE, defined as intravenous TPE infusion (12 mL TPE dissolved in 250 mL 5% Glucose Injection) once daily for 7 days on the background of standard treatment after PCI; 124 who did not receive TPE were regarded as the control group and received standard treatment after PCI. The corrected thrombolysis in myocardial infarction frame count (CTFC) and index of microcirculatory resistance (IMR) were used to evaluate myocardial microcirculation. Cardiac function was measured by echocardiography during hospitalization and follow-up. Major adverse cardiac events (MACEs) were recorded for prognostic analysis.Results: At the 6-month follow-up, AMI patients who received TPE after primary PCI had significantly lower levels of CTCF (24.27±2.40 vs. 21.88±1.92, P<0.001) and IMR (20.02±2.20 vs. 17.80±2.11, P<0.001) than patients in the control group. Left ventricular ejection fraction and left ventricular internal dimension at systolic at 6-month follow-up in the TPE group significantly improved than in the control group (56.6±4.5 vs. 62.1±3.5, P<0.001; 32.5±1.5 vs. 30.2±1.8, P<0.001). Kaplan-Meier curve analysis indicated that patients with AMI who received TPE had significantly lower rates of MACEs than the control group at 6-month follow-up (P=0.042).In the context of standard treatment, Trichosanthes pericarpium further improved coronary microcirculation, increased cardiac function, and reduced short-term MACEs rate. Our data suggest that TPE could be used in combination therapy for patients with AMI after primary PCI.